2011
DOI: 10.3201/eid1703.100167
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliO157 Infection and Secondary Spread, Scotland, 1999–2008

Abstract: To determine the proportion of Escherichia coli O157 cases in Scotland attributable to secondary spread, we analyzed data obtained through entire-population enhanced surveillance. We identified 11% of cases as secondary. Secondary cases in single households were younger than secondary cases in outbreaks affecting >1 household and had similar risk for hemolytic uremic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 13 publications
6
31
0
Order By: Relevance
“…While this represents a significant reduction from previous years, the incidence of infection in the United States remains 7-fold higher than the incidence in Australia (0.12 cases per 100,000) (9). Furthermore, the rate of infection in Scotland has been reported at 4.4 cases per 100,000, 36-fold higher than Australia (10). Although there is currently no direct information available on the frequency of infection in Argentina, the incidence of HUS in that country is among the highest in the world (12) and most cases of HUS in this region have been attributed to E. coli O157 (6,12,14).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…While this represents a significant reduction from previous years, the incidence of infection in the United States remains 7-fold higher than the incidence in Australia (0.12 cases per 100,000) (9). Furthermore, the rate of infection in Scotland has been reported at 4.4 cases per 100,000, 36-fold higher than Australia (10). Although there is currently no direct information available on the frequency of infection in Argentina, the incidence of HUS in that country is among the highest in the world (12) and most cases of HUS in this region have been attributed to E. coli O157 (6,12,14).…”
mentioning
confidence: 82%
“…Maximum parsimony analysis showed that the majority of Australian isolates (PG4 and PG6) were closer to branches overrepresented by U.S. cattle isolates (PG5) than to branches containing a higher proportion of U.S. human isolates (PG1, PG2, and PG3). The incidences and severities of disease caused by E. coli O157 differ substantially worldwide (9)(10)(11)(12)(13). In comparison to many countries, including the United States, Australia has a low reported incidence of infection (9).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of contaminated food such as raw or undercooked ground meat products, raw milk, vegetables, fruits and well water is a common cause of STEC infections. Person-to-person transmission of STEC infection has also been reported (Locking et al, 2011;Rangel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This pathogen continues to cause most of known outbreaks across the globe. 3,4 Therefore, the US Department of Agriculture (USDA) has enforced a "zero tolerance policy" to regulate the prevalence of O157:H7 in foods. Genetic methods, most commonly the lineage specific polymorphism assay (LSPA) 5 and clade typing, 6 have been used to separate O157:H7 strains by virulence potential and ecology.…”
Section: Introductionmentioning
confidence: 99%